Assessing the Adaptive Mechanisms of Two Bread Wheat (Triticum aestivum L.) Genotypes to Salinity Stress - Ulkar Ibrahimova; Zarifa Suleymanova; Marian Brestic; Alamdar Mammadov; Omar M. Ali; Arafat Abdel Hamed Abdel Latef; Akbar Hossain (Agronomy, 2021)
This work deals with the assessment of physiological and biochemical responses to salt stress, as well as the regulation of the expression of the K+/Na+ transporter gene-TaHKT1;5 of two Triticum aestivum L. genotypes with contrasting tolerance. According to the observations, salinity stress caused lipid peroxidation; accumulation of soluble sugars and proline; decreased osmotic potential, Fv/Fm value, and K+/Na+ ratio; and increased the activity of antioxidant enzymes in both genotypes. In the salt-tolerant genotype, the activity of enzymes, the amounts of soluble sugars and proline were higher, the osmotic potential and the lipid peroxidation were lower than in the sensitive one, and the Fv/Fm value remained unchanged. A comparison of the accumulation of Na+ and K+ ions in the roots and leaves showed that the Na+ content in the leaves is lower. The selective transport of K+ ions from roots to leaves was more efficient in the salt-tolerant genotype Mirbashir-128; consequently, the K+/Na+ ratio in the leaves and roots of this genotype was higher compared with the sensitive Fatima genotype. The semi-quantitative RT-PCR expression experiments on TaHKT1;5 indicated that this gene was not expressed in the leaf of the wheat genotypes. Under salt stress, the expression level of the TaHKT1;5 gene increased in the root tissues of the salt-sensitive genotype, while it decreased in the salt-tolerant wheat genotype. The results obtained suggest that the ion status and salt tolerance of the wheat genotypes are related to the TaHKT1;5 gene activity.